The ailing welfare state - Segado Sánchez-Cabezudo, Sagrario; López Peláez, Antonio (Cizur Menor, Navarra Aranzadi, 2016)
In the wake of the financial crisis, citizens are demanding more and better benefits, more effective management, and greater participation. In order to reform our welfare state with the necessary guarantees, we must ask two questions. First, how have austerity policies affected our lifestyle and our social protection system? And, second, how should we redefine our welfare system in the coming years? Can we return to the benefits and services model prior to the crisis? Should we redefine it? The answer to both questions is obvious: we need to redefine our welfare model. To do so in a setting where resources are always scarce, we need to include groups that until now have been invisible and not received support, and we need to rethink our benefits and services. It is not enough simply to return to things as they were before, with its winners and losers, nor should we continue with the current dynamics, which also has its winners and losers. Throughout this process, the middle classes play a key role as a benchmark (in an aspirational society the expectation of upward social mobility bonds individuals to their environment), resource providers (through taxes), and claimants seeking benefits and services. The factors influencing processes of downward social mobility must be examined in order to design public policies that take into account the specific problems affecting the middle classes The best contribution we can make to our future is to analyze with rigor the challenges we face. Greater social cohesion and a higher level of welfare can only be achieved by enhancing participation, assessing the results of our social policies more thoroughly, and more democracy. The various chapters provide insight into the issues faced by the middle classes, and propose alternatives for the future.
Keywords: Economía